2020
DOI: 10.1111/jipb.12917
|View full text |Cite
|
Sign up to set email alerts
|

H3K36me2 is highly correlated with m6A modifications in plants

Abstract: The intimate linkage between H3K36me3 and m 6 A modifications has been demonstrated in mammals. In this issue, Shim et al. (2020) show that similar crosstalk between histone modification and mRNA methylation is conserved in plants, but H3K36me2 is more important for m6A deposition in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
0
16
0
1
Order By: Relevance
“…Indeed, previously, it was shown that salinity‐responsive m 6 A peak containing transcripts of Arabidopsis were more stable under salt stress (Anderson et al., 2018). There are other potential mechanisms leading to increased transcript abundance such as possible interactions of m 6 A writer or reader complexes with histone modifications to affect RNA transcription (Huang et al., 2009; Shim et al., 2020). Based on our data alone, it is hard to predict whether this change in mRNA abundance of the cold‐enriched m6A containing transcripts is the result of an increased stability or enhanced transcription, or a combination of both, and this needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previously, it was shown that salinity‐responsive m 6 A peak containing transcripts of Arabidopsis were more stable under salt stress (Anderson et al., 2018). There are other potential mechanisms leading to increased transcript abundance such as possible interactions of m 6 A writer or reader complexes with histone modifications to affect RNA transcription (Huang et al., 2009; Shim et al., 2020). Based on our data alone, it is hard to predict whether this change in mRNA abundance of the cold‐enriched m6A containing transcripts is the result of an increased stability or enhanced transcription, or a combination of both, and this needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…m 6 A refers to the methylation of the adenosine base at the nitrogen‐6 position, which is the most prevalent internal modification of eukaryotic mRNAs (Dominissini et al, 2012, 2013; Yue et al, 2015; Arribas‐Hernandez et al, 2018). m 6 A regulates almost every aspect of mRNA processing and metabolism, of which alternative polyadenylation (APA) is an important post‐transcriptional regulatory mechanism that can generate different mRNA isoforms (Jia et al, 2011; Zheng et al, 2013; Liu et al, 2014; Ping et al, 2014; Wang et al, 2014, 2015; Shim et al, 2020). Cleavage and Polyadenylation Specificity Factor 30 (CPSF30) is a key polyadenylation factor which has two isoforms, the short one named CPSF30‐S and the longer one termed CPSF30‐L, which contains an additional YT512B Homolog (YTH) domain that is established as a m 6 A binding domain.…”
Section: Emerging Roles Of Phase Separation In Plantsmentioning
confidence: 99%
“…I n eukaryotic cells, histones and DNA are packed and ordered into highly structured units called nucleosomes. Nucleosomal histones are subject to multiple posttranslational modifications, such as methylation, acetylation, phosphorylation, and ubiquitination, which play critical roles in various biological processes that include transcriptional regulation, chromosome packaging, and repair of DNA damage (Bannister and Kouzarides, 2011;Zhao et al, 2019;Shim et al, 2020). Acetylation of histones occurs at specific lysine residues on their N-terminal tails and is associated with transcriptional activation (Struhl, 1998).…”
Section: Introductionmentioning
confidence: 99%